Influence of corrosion on lipopolysaccharide affinity for two different titanium materials - Barão, Valentim Adelino Ricardo; Mathew, Mathew T.; Yuan, Judy Chia-Chun; Knoernschild, Kent L.; Assunção, Wirley Gonçalves [UNESP]; Wimmer, Markus A.; Sukotjo, Cortino (Elsevier, 2013)
Titanium is subject to corrosion in the oral cavity, which could contribute to periimplantitis. However, the effect of corrosion on the lipopolysaccharide affinity for titanium remains unknown. This study evaluated the role of corrosion (in artificial saliva at pHs 3, 6.5, and 9) on the lipopolysaccharide (LPS) affinity for commercially pure titanium (cp-Ti) and Ti-6Al-4V alloy. Seventy-two titanium disks were anodically polarized in a controlled environment (n=9). Control specimens were not corroded. Deionized water with different concentrations of LPS (1.5, 15, and 150 μg/mL) were used to treat the disks for 24 hours to investigate LPS adherence (n=3). Then specimens were immersed in LPS-free water to evaluate LPS elution at 24, 48, and 72 hours. Data were analyzed by the 2-way, 3-way, and 3-way repeated measures ANOVA, t tests, and the Tukey honestly significant difference (HSD) tests (α=.05). A greater corrosion rate of cp-Ti and Ti-6Al-4V alloy and a higher LPS adherence to titanium surfaces (P<.05) were noted at acidic pH. The LPS affinity was higher for the Ti-6Al-4V alloy than for cp-Ti (P<.05). More LPS was eluted from titanium surfaces after a 24-hour interval. Lipopolysaccharide affinity for cp-Ti and Ti-6Al-4V alloy is influenced by the corrosion process.